Consumer Response Analysis to Steamed Red Bean Flour Cake - Suni, Muh. Irdiansyah (Gastronary, 2022)
The title of this research is "Analysis of Consumer Response to Red Bean Flour Steamed Cake". The background of this study describes the use of red bean flour as a substitute for wheat flour in making steamed sponge cake. This is because the use of wheat flour is very high in Indonesia and is a food ingredient that is still imported. This study aims to determine consumer responses to red bean flour processed into steamed sponge cake. This research method is a type of qualitative experimental research. The research location is JL. Kedawung, Nologaten Rt 05/02, Catur Tunggal, Depok, Sleman, Yogyakarta, the research time is November 2021. The data analysis method of this research is the hedonic test or preference test with the Microsoft Excel program. The results of this study indicate that the aroma indicator has an average of 3.8 and a percentage of 70% with the criteria of liking, the texture indicator has an average of 4.2 and a percentage of 84% with the criteria of very like and the taste indicator has an average of 4.33 and a percentage of 86.67. % with the criteria of really liking the colour indicator having a mean of 4.27 and a percentage of 72%. So it can be concluded that respondents like red bean flour steamed cake from the aspect of aroma, texture and taste, and red bean flour can be used as a substitute for wheat flour in making steamed sponge products